PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN DI DESA PAJARAKAN KULON KECAMATAN PAJARAKAN - Fathullah, Kholidazia El Hamzah (STIH Zainul Hasan Kraksaan Kraksaan, 2022)
Abstract One of the roles of the government towards its citizens in running the government is to provide public services. One of these public services is the BPJS Health service. The purpose of this study is to find out BPJS Health Services to the community using the National Health Insurance in Pajarakan Kulon Village, the benefit is that this research is expected to provide information and knowledge to determine the relationship between BPJS user satisfaction and the Quality of Health Insurance Services. National in BPJS Health. the method used is using the Juridical Empirical method by combining primary and secondary data obtained from the field in the form of interviews and other legal sources. This thesis research is about BPJS Health Services in the implementation of the good governance-based National Health Insurance (JKN) program at BPJS Kesehatan Kraksaan. The conclusions obtained are the categories that exist in BPJS Health Law number 24 of 2011. The advice drawn is that BPJS health users should be able to reach the maximum and make registration easier for new users who want to use BPJS because it will affect the quality of BPJS in BPJS Kesehatan. Keywords: Quality of Health Services, BPJS Health